Pengembangan E-Modul Minyak Bumi Berbasis Pendekatan Saintifik untuk Kelas XI SMA/MA - Emira Eldina Ihsan; Hardeli Hardeli (Entalpi Pendidikan Kimia, 2021)
ABSTRACT The subject matter of petroleum at school is still difficult for students to be understand because of the length of the material description, many concepts using foreign terms, and the visualization of petroleum material in the teaching materials has not attracted enough attention. One way to obtain teaching materials that can increase students' motivation and understanding is to develop e-module teaching materials. E-modules also allow students to learn independently. The e-module was developed using a scientific approach as suggested in the 2013 curriculum. This study aims to develop a valid e-module. The type of research conducted is Educational Design Research. The e-module was developed using the Plomp development model which consists of three main steps, preliminary research stage, prototype stage and assessment phase. This research is limited to the validation stage. Validation was carried out by 5 validators, by three chemistry lecturers at FMIPA UNP and two chemistry teachers. The validation results are calculated using Aiken’s V statistics. From the results of data processing, it is found that the petroleum e-module based on the scientific approach developed is valid with value 0.83. Keywords: Educational Design Research, Independent Learning, Petroleum, Scientific Approach